2014
DOI: 10.1136/vetreccr-2014-000105
|View full text |Cite
|
Sign up to set email alerts
|

Acute onset of blindness secondary to a splenosystemic shunt in an adult cat

Abstract: An eight-year-old female, spayed, domestic, shorthair cat was presented for acute onset of blindness, lethargy, dysorexia and weight loss. On the basis of clinical presentation, clinicopathological findings, liver function tests and diagnostic imaging, a diagnosis of hepatic encephalopathy secondary to the presence of a hepatic vascular anomaly was made. The patient responded successfully to medical treatment. This case raises the importance of considering a portosystemic shunt as a possible cause of acute ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…25 Another common complication in cats with EHPSS before and after attenuation is acute central blindness. 3,4,6,7,8,9,26 Blindness that occurs secondary to hepatic encephalopathy is usually accompanied by other clinical signs, including ataxia, head pressing, and circling. 27 In this study, five cats had either persistent or intermittent blindness prior to surgery, and two developed postoperative blindness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Another common complication in cats with EHPSS before and after attenuation is acute central blindness. 3,4,6,7,8,9,26 Blindness that occurs secondary to hepatic encephalopathy is usually accompanied by other clinical signs, including ataxia, head pressing, and circling. 27 In this study, five cats had either persistent or intermittent blindness prior to surgery, and two developed postoperative blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Another common complication in cats with EHPSS before and after attenuation is acute central blindness 3,4,6,7,8,9,26 . Blindness that occurs secondary to hepatic encephalopathy is usually accompanied by other clinical signs, including ataxia, head pressing, and circling 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Splenosystemic shunts are a unique subtype that draw significant parallels to the mesentericorenocaval shunt identified. 13,25 In a retrospective study of 33 afflicted cats, a single vascular communication was identified from the splenic vein and terminating in either the left renal vein or CdVC. 13 The definitive aetiology similarly remains open; Palerme et al hypothesise that these represent congenital shunts with minimal clinical significance, and their identification during investigations of vomiting or inappetence was completely incidental.…”
Section: Discussionmentioning
confidence: 99%